2023
DOI: 10.3390/ijerph20032475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Plyometric Training on the Jump Performance of Elite Male Handball Players: A Systematic Review

Abstract: Handball is one of the most popular team sports around the world that has become physically very demanding, related to both competitions and daily training sessions. Optimal training programs are necessary to improve performance, especially when taking into account the frequency of jump shots (vertical jumps) and handball feints (changes of directions) during daily training. The main objective of the present study is to review the available literature systematically, and to determine what are the effects of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The research results showed no significant difference between the two groups in Ergo-jump variables. In contrast, other studies have shown that Plyometric training improves performance and maintains explosive strength parameters 54 , 55 . Villarreal et al (2011) report improvements in Power Output, Maximum Rate of Force Development, and Height in Countermovement Jump after plyometric training 56 .…”
Section: Discussionmentioning
confidence: 71%
“…The research results showed no significant difference between the two groups in Ergo-jump variables. In contrast, other studies have shown that Plyometric training improves performance and maintains explosive strength parameters 54 , 55 . Villarreal et al (2011) report improvements in Power Output, Maximum Rate of Force Development, and Height in Countermovement Jump after plyometric training 56 .…”
Section: Discussionmentioning
confidence: 71%
“…Based on previous studies, we chose the standing long jump (SLJ) and countermovement jump (CMJ) to test the effect of DJ on lower limb explosive, 6 , 7 , 15 , 16 , 20 , 21 and the Illinois agility test, square test, Nebraska test, T-Test, and hexagon test to test the effect of DJ on CoD performance in collegiate Sanda athletes. 13 , 14 , 15 , 16 All tests were done in one day, with SLJ, CMJ, Nebraska test, and T-Test in the morning and hexagon test, square test, and Illinois agility test in the afternoon.…”
Section: Methodsmentioning
confidence: 99%
“…Plyometric training (PT) is a well-known form of “ballistic training,” which refers to a wide range of jumping, bounding, and hopping exercises involving high-intensity stretching of a muscle (eccentric contraction) immediately followed by a rapid and powerful concentric contraction of the same muscle and connective tissue. 5 As PT can produce more force than can be provided by a concentric-only muscle action alone, researchers have shown that PT is an effective method for improving jumping abilities, 6 , 7 balance, 8 explosive performance, 8 , 9 strength, 8 , 10 speed, 11 running economy, 12 agility, 13 , 14 endurance performance, 8 , 9 and CoD ability. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Despite handball being a sport that already incorporates a considerable number of plyometric actions like jumping and changes of direction, Jakšić et al (2023) considered that there is value in adding PT exercises to regular handball training. A study by emphasizes the importance of performing exercises in different movement vectors to improve change of direction (COD) and the ability to move in different directions.…”
Section: Type Of Exercises (And If They Were Sportspecific/involving ...mentioning
confidence: 99%
“…Although previous systematic reviews (with meta-analysis or scoping focuses) addressed the effects of PT, these did not include analyses of upper-body plyometric training methods (Ramirez-Campillo, et al, 2020a), and they focused on sports other than handball (Ramirez-Campillo, et al, 2020b). In a more recent development, a systematic review (Jakšić, et al, 2023) delved into the impacts of supplementary plyometric training on jump performance of elite handball players. Nonetheless, it is crucial to highlight that this particular review centers solely on lower-limb plyometric training and its distinct effect on vertical jump performance.…”
Section: Introductionmentioning
confidence: 99%